-2(6x-4)=8-12*x

Simple and best practice solution for -2(6x-4)=8-12*x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(6x-4)=8-12*x equation:


Simplifying
-2(6x + -4) = 8 + -12x

Reorder the terms:
-2(-4 + 6x) = 8 + -12x
(-4 * -2 + 6x * -2) = 8 + -12x
(8 + -12x) = 8 + -12x

Add '-8' to each side of the equation.
8 + -8 + -12x = 8 + -8 + -12x

Combine like terms: 8 + -8 = 0
0 + -12x = 8 + -8 + -12x
-12x = 8 + -8 + -12x

Combine like terms: 8 + -8 = 0
-12x = 0 + -12x
-12x = -12x

Add '12x' to each side of the equation.
-12x + 12x = -12x + 12x

Combine like terms: -12x + 12x = 0
0 = -12x + 12x

Combine like terms: -12x + 12x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -6d=-8 | | 6-3x+2x^2-x^3=0 | | -x=7x+2 | | 4*x+19=-9-6x | | x+5=7x+2 | | 25-(-5)-7= | | 3x-22+65=180 | | 5=18a | | 3+x-4=7x-2 | | 2u^2+3u-20=0 | | 4*x+3=2(2x+9) | | (x-8)=x-3 | | 6+2(2-4x)=6x+2(2x-4) | | 30+40x=35 | | 55=285-10e | | 2(6x+10y)+8=0 | | 4(x-6)-10=2x | | b=11-a | | 2(x-4)-6=-6(-2x+4)-6x | | 6r+5=55 | | k+3=6+k | | 30+(.0825*30)+(15%*30)= | | 6(y+2)=-2(8y-7)+6y | | -26+26=-15p-10p | | 11x-4=5x+9 | | x*12=-2 | | X+3(4)=48 | | 3x+10=3x+4+1 | | 2(x-1)-3x=8 | | 8-2x=2x-5x | | 1x+3(4)=48 | | 9(-10)+160= |

Equations solver categories